Analysis of Pedagogic Content Knowledge Technology (TPCK) Capabilities of Teachers in Senior High School - Hasriadi Hasriadi; Nurul Nurul (Didaktika: Jurnal Kependidikan, 2023)
This study investigated the ability of Pedagogic Content Knowledge Technology (TPCK) of teachers in Senior High School. This study aims to assess and analyze (1) the ability of TPCK teachers and (2) its application in the context of learning in the school. The qualitative approach is descriptive, and data is obtained through observation, interviews, and documentation. The results showed that, although the teachers had demonstrated good TPCK skills, there were variations in the level of mastery between them. In terms of application, teachers have integrated technology well into the learning process, although they still face obstacles related to network infrastructure. This research illustrates the complexity of teachers' TPCK capabilities in today's technological era, highlights their success in overcoming challenges, and offers recommendations for improving the use of technology in learning. These findings provide important insights for future educational pedagogy and policy development.